DR. JEKYLL DAN MR. HYDE: SEBUAH PENGGAMBARAN DUALISME NALURI KEHIDUPAN DAN KEMATIAN - Eka Putri Alda, Rizki (Adabiyyāt: Jurnal Bahasa dan Sastra, 2020)
According to Freud, the life instinct (Eros) and the death instinct (Thanatos) can be compatible despite the fact that the life instinct was purposedly to maintain the continuity of life while the death instinct aims to dispel the life. The purpose of this study is to elaborate the concept of dualism between the life and death instincts in R.L. Stevenson’s The Strange Case of Dr. Jekyll and Mr. Hyde. The researcher used qualitative research methods to process and analyze the data. The result of this study found that the main character Henry Jekyll had behaviors which contradict the Victorian norms that made he thought he had dualism within. Jekyll did action to separate the bad sides of him by the chemical practices. The fact that both life and death instincts worked collectively made Jekyll’s plans cannot reach its goals. The madness due to the ideal self-concept which had a tendency towards narcissistic pathology was finally destroyed as a result of colliding with reality. This situation resulted Henry Jekyll lost the meaning of his life as the symbol of psychical death, which at the end of the story, it continued with real death of Jekyll's body.